Luq and Nana in search of Asian elephants: a narrative based motion comic / Ahmad Imran Mansur - Mansur, Ahmad Imran (Faculty of Art and Design, 2020)
In the distant future in Malaysia. The young Luq and Nana find a rather peculiar creature in one of their grandfather's photo albums, first thought to be an alien, Tok Yusof explains it is actually a near-extinct animal, named as the Asian Elephant.